Effect of electronic government on telemedicine: a narrative review - Castro-Uceda, Maria Fernanda (2025)
ABSTRACT Introduction: The impact of e-government on telemedicine can be significant, as it facilitates the implementation of policies and regulations that promote its adoption, improves the necessary technological infrastructure, and ensures data security and privacy. Material and methods: A search of scientific literature was carried out in the following databases: Scopus, Pubmed, Web of Science, Lilacs and Scielo. Articles from the years 2020 to the present, written in any language and open access were considered; after applying inclusion criteria, a total of 26 articles were obtained. Results: Globally, telemedicine has improved access and efficiency in physician care, especially in remote areas. However, resistance to change, the digital divide and lack of technological readiness remain critical obstacles, especially in developing countries. Training, education, social support and strategies adapted to local realities are key to overcoming technological and human barriers, promoting a more equitable and effective adoption of digital health technologies. Conclusion: There are advances and challenges in the integration of e-health with e-governance, although problems of data fragmentation, security and lack of resources persist, especially in developing countries, where infrastructure and policy limitations are more pronounced.